The effect of palonosetron hydrochloride in the prevention of chemotherapy-induced moderate and severe nausea and vomiting - HUANG, JIAN (D.A. Spandidos, 2013)
The current study aimed to evaluate the efficacy and safety of palonosetron hydrochloride injection for preventing chemotherapy-induced moderate and severe nausea and vomiting. A multi-centered, randomly stratified, double-blind, double-dummy, parallel-group and positive-controlled trial was performed. A total of 240 patients who underwent chemotherapy treatment which induced moderate or severe vomiting were divided into the experimental and control groups. Half an hour before chemotherapy, the experimental group received a 0.25-mg palonosetron hydrochloride injection, whereas the control group received a 3-mg granisetron injection. The acute vomiting complete remission rate (CRR) of the experimental group was not significantly different compared with that of the control group (P=0.35). The delayed vomiting CRR of the experimental group was significantly higher compared with that of the control group (P=0.002). No difference in full course vomiting CRR, vomiting control time, treatment failure time or acute nausea CRR was identified between the two groups. No significant differences in adverse events were observed between the experimental group and the control group. No significant differences in adverse reactions occurred between the experimental group and the control group (12.50%). Palonosetron hydrochloride injection had a better effect on delayed vomiting CRR than granisetron hydrochloride injection. The two injections exhibited similar effects on acute vomiting CRR, full course vomiting CRR, vomiting control time, treatment failure time (days), acute nausea CRR and adverse events.